Analisis Of The Organic Vegetable Supply Chain (case study of the modern market behind soybenas in Ambon City) - Koce Telapary; Dr. S.F.W. Thenu, S.P., M.Si; Fioletta Papilaya, S.P., M.Si (International Journal of Economics, Business and Innovation Research, 2024)
Abstract This research aims to determine the supply chain of organic vegetables in the Fris Behind Soya modern market, Ambon City and determine the marketing margin and marketing efficiency in the supply chain. The data collected in this research is primary data and secondary data. The results of this research show that kale and spinach vegetables in Passo village are harvested and then entrepreneurs carry out the process of washing, packing, labeling and continuing to the Fris supermarket distributor and consumers as end users. The supply chain for hydroponic vegetables in Fris supermarkets is through a supply chain, namely: organic entrepreneurs → Fris supermarkets → consumers. Marketing kale and spinach vegetables provides a profit of IDR 5,236, but does not meet the demand from Fris supermarkets. Entrepreneurs choose to sell to Fris supermarkets because the continuity of vegetable supply is more guaranteed. Two types of organic vegetables that are widely cultivated by organic entrepreneurs are kale and spinach. The number of kale vegetables is 30 packages and 40 packages of spinach for one delivery. Organic vegetable entrepreneurs maintain good relations with Fris supermarkets.